A Systematic Review of Sleep-Wake Disturbances in Childhood Traumatic Brain Injury: Relationship with Fatigue, Depression, and Quality of Life. Issue 4 (July 2019) - Botchway, Edith N.; Godfrey, Celia; Anderson, Vicki; Catroppa, Cathy
Abstract : Objective: To systematically appraise the literature on the prevalence, types, and predictors of sleep-wake disturbances (SWD), and on the relationship between SWD, fatigue, depression, and quality of life in children and adolescents with traumatic brain injury (TBI). Methods: MEDLINE, PubMed, PsychInfo, Web of Science, and EMBASE databases were searched, reference lists of retrieved articles were also searched for relevant articles, and study methods were evaluated for risk of bias. Results: Of the 620 articles assessed, 16 met inclusion criteria. Sleep-wake disturbances were common in childhood TBI. The most common types of SWD reported were insomnia and excessive daytime sleepiness, with mild TBI participants showing a trend toward more sleep maintenance insomnia, while sleep-onset insomnia was typical in those with moderate-severe TBI. Predictors of SWD reported in studies involving mild TBI participants included TBI severity, male sex, preexisting SWD, high body weight, and depression; while injury severity and internalizing problems were associated with SWD in moderate-severe TBI participants. Sleep-wake disturbances were also associated with fatigue and poor quality of life following TBI. Conclusion: Sleep-wake disturbances are highly prevalent in childhood TBI, regardless of injury severity. Routine assessments of SWD in survivors of childhood TBI are recommended.